Reflections on the judiciary justice delivery over 75 years - Lokur, Madan B. (The Journal of Governance)
The first sitting of the Supreme Court of India was on 28th January 1948 in the Chamber of Princes in what is today known as Parliament House. The Supreme Court shifted to its present home much later in 1958.- Reproduced